PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT DALAM MEMBACA PEMAHAMAN BAHASA ARAB (Universitas Negeri Semarang, 2012)
a stagnant learning the skills of reading makes students less interested in learning to read so that students are lazy to read. One effort to improve reading skills is to implement cooperative learning model TGT. This learning model engages students into their respective groups, where each group will play each other in accordance with the level of ability of each student. Analysis of test results showed that the experimental class at the pretest to obtain an average value of 73.95 in all aspects. While the control class at the pretest scored 71.60. Treated after experimental class scored an average of 79.65 while the control class untreated obtain rata72 average, 25. Having calculated by the formula t ttest experimental class had greater than ttabel ie t = 5.00> t table = 2.02. So based on these calculations it can be concluded that cooperative learning model TGT effective for improving reading comprehension skills